Role of Magnesium in Health and Disease - Emila, S; Swaminathan, S (Journal of Experimental Sciences, 2013)
The list of conditions related to magnesium deficiency is quite high. The National Institute of Health information says that magnesium is a wonder drug but its use in clinical medicine is very scarse. Magnesium deficiency has been implicated in a wide range of clinical conditions such as insomnia, crumps, diarrhea, erectile dysfunction, headache, migrane, low blood pressure, loss of appetite, nausea, vomiting, weakness, numbness, tingling, seizures, personality change, abnormal heart rhythms, coronary spasms, cardio vascular disease, type 2 diabetes mellitus, depression, immune dysfunction, thyroid function alterations to name a few. Although supplementation is said to restore normalcy in a majority of cases, very few studies have been done in this direction. The role of magnesium in alleviating cancers of all types has been extensively studied, but treatment using magnesium is very limited. This review article aim to bring out research findings during the last 3 decades on the role magnesium in health and disease and this will enable researches to understand in detail and give awareness about further works to be carried out in this field, with an ultimate aim of using magnesium as a drug to cure a host of diseases.